2020
DOI: 10.1111/ppc.12504
|View full text |Cite
|
Sign up to set email alerts
|

Effects of technology usage on the addictive behaviors of secondary school students

Abstract: This study aimed to evaluate the relationship between technology usage and technology addiction among secondary school students. Design and Methods: This descriptive research was conducted in April 2018 with 840 students in Eastern Turkey. Findings: The average Internet and digital-gaming addiction scores of the participating students were found to be significantly higher among those who used computers, smartphones, and tablets daily and for long periods of time. Implications for Practice: Using technological … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…5 However, although the appropriate and controlled use of ICT may improve students' academic achievement, and help them to better communicate and socialize, using it in a pathological way can lead to increasing levels of addiction, especially among the young. 1,6,7 In the literature, a number of different dimensions of addiction have been examined, including internet addiction, smartphone addiction, and social media addiction among others. 8,9 The improper use of ICT is likely to negatively affect work performance, social relations, effective time management, and mental and psychological health.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations
“…5 However, although the appropriate and controlled use of ICT may improve students' academic achievement, and help them to better communicate and socialize, using it in a pathological way can lead to increasing levels of addiction, especially among the young. 1,6,7 In the literature, a number of different dimensions of addiction have been examined, including internet addiction, smartphone addiction, and social media addiction among others. 8,9 The improper use of ICT is likely to negatively affect work performance, social relations, effective time management, and mental and psychological health.…”
Section: Introductionmentioning
confidence: 99%
“…8,9 The improper use of ICT is likely to negatively affect work performance, social relations, effective time management, and mental and psychological health. 3,6,9 For students with internet addiction, the use of ICT is highly probable to have a negative effect on academic performance. Only a limited number of studies have been published in the last 5 years about technology addiction and its relationship to academic achievement in nursing students who use ICT, including e-learning, as part of their theoretical and practical education.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The fact that boys are more interested and curious about digital media tools and their contents may be effective in such results. Similarly, in the literature, it was concluded that the screen time spent in various digital media tools is higher in boys ( Öztürk Eyimaya & Yalçın Irmak, 2021 ; Furuncu & Öztürk, 2020 ; Taş & Güneş, 2019 ; Gürarslan Baş & Karatay, 2020 ).…”
Section: Discussionmentioning
confidence: 78%